Implicações da teoria histórico-cultural no processo de formação de professores da educação infantil - Magalhães, Cassiana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis is a result of research on Implications of Historical-Cultural Theory in Teacher Education of Early Childhood Education held in a Child Education Centre of the City of Londrina-PR, with the participation of eight teachers working with 0 to 5- year-old children. It aimed to understand possible changes in pedagogical practice of teachers participating in the research study from the Historical-Cultural Theory, based on the following hypothesis: Education is an objectification of the sphere of non-daily activity, of the complex sphere of human activity. Therefore, it is an activity that requires reflection, intention, theoretical foundation. However, the logic that has guided teaching is the logic of everyday life. The problem of this research is presented as follows: How can we impact the teaching job in humanizing perspective through the Historical-Cultural Theory? To answer the question, data were generated in 2012 with the completion of the weekly group studies in the first semester and biweekly in the second half. Each study generated an individual reflection writing used in the research analysis. Besides the reflections, eighteen observation sessions occurred in classrooms of the participating teachers. Data were analyzed focusing on the following concepts and their embodiments in practices observed: Learning and Development; Education as a Humanization process; The organization of teaching practice. The results indicated that the practice of reading texts which explain Historical-Cultural Theory provides bases to impact the teaching work qualitatively affecting the practices toward a developmental education. These results were shown in the teachers’ conceptions on the concepts of child, school, and teacher, and led to changes in teaching practices in relation to the organization of the space, the place of children in relationships experienced in school, to the child’s place in planning daily activities and to the...

A presente tese é resultado de uma pesquisa sobre Implicações da Teoria Histórico- Cultural na Formação dos Professores da Educação Infantil realizada em um Centro Municipal de Educação Infantil da cidade de Londrina-PR, com a participação de oito professoras atuantes com crianças de zero a cinco anos de idade. Teve como objetivo principal compreender possíveis transformações na prática pedagógica dos professores participantes da pesquisa a partir do estudo da Teoria Histórico-Cultural, partindo da seguinte hipótese: a educação é uma objetivação da esfera da atividade não cotidiana, da esfera complexa da atividade humana. Portanto, é uma atividade que exige reflexão, intenção, fundamentação teórica. No entanto, a lógica que tem orientado o trabalho docente é a lógica do cotidiano. O problema desta pesquisa se apresentou da seguinte forma: Como podemos impactar o trabalho pedagógico docente numa perspectiva humanizadora por meio da Teoria Histórico-Cultural? Para responder ao questionamento, a geração de dados aconteceu no ano de 2012 com a realização de grupo de estudo semanais no primeiro semestre e quinzenais no segundo semestre. Cada estudo gerou uma reflexão individual escrita utilizada na análise da pesquisa. Além das reflexões aconteceram dezoito sessões de observação nas turmas das professoras participantes. Os dados foram analisados focando as seguintes concepções e suas concretizações nas práticas observadas: Aprendizagem e Desenvolvimento; Educação como processo de Humanização; A organização das práticas pedagógicas. Os resultados indicaram que a prática da leitura de textos que explicam a Teoria Histórico-Cultural fornece bases para impactar o trabalho docente, afetando qualitativamente as práticas em direção a uma educação desenvolvente. Tais resultados foram evidenciados nas concepções das professoras acerca dos conceitos de criança, escola, papel do professor...
Keywords: Educação de crianças; Professores - Formação; Aprendizagem social; Teachers, Training of